Importance of transformational leadership in project success: a theoretical framework - Khan, Saifur (National Academy of Management, 2015)
The article theoretically supports the fortification of the existing transformational leadership models and their relationship with project success. The study addresses this theoretical gap by discussing different leadership theories because project leadership is sourced from general leadership theories, contributing to better understanding and suggesting implementation of a combination of leadership models